On homoclinic chaos and a control chaos strategy applied to a free-joint nonholonomic manipulator - Cassiano, Jefferson; Balthazar, José Manoel [UNESP] (World Scientific Publ Co Pte Ltd, 2007)
In this work, the occurrence of chaos (homoclinic scene) is verified in a robotic system with two degrees of freedom by using Poincare-Mel'nikov method. The studied problem was based on experimental results of a two-joint planar manipulator-first joint actuated and the second joint free-that resides in a horizontal plane. This is the simplest model of nonholonomic free-joint manipulators. The purpose of the present study is to verify analytically those results and to suggest a control strategy.
Keywords: chaos; control; Poincare-Mel'nikov method; nonholonomic manipulator